How the Demand for Labor May Adapt to the Availability of Labor: A Preliminary Exploration with Historical Data - Harriet Duleep; Xingfei Liu (Institute for the Study of Labor (IZA), 2015)
This note presents and tests a general model to help explain why the demand for labor adapts to the availability of labor. In particular, we postulate that the cost of hiring declines with a growth in available labor for two reasons: (1) individuals seeking employment would be coming to employers instead of the latter seeking them out and (2) the larger set of potential employees would increase the probability of employers finding individuals suitable for unfilled jobs. Moreover, individuals seeking employment likely encourage employers to think of new ways in which labor can be used. An increase in the number of entrants to the labor force would lower the cost of hiring and increase employment demand at any given wage rate. Hence, a change in the labor force - such as the addition of women or immigrants - does not increase unemployment as much as is predicted for current workers because demand for labor increases as the cost of hiring decreases. Failure to taken into account what we term an - "encouraged employer effect" may also explain why surges in employment are often underestimated.
Keywords: J20; J21; J23; 330; labor demand; hiring cost; encouraged employer effect; labor force